Brand Architecture and Branding Strategy of B2C Product and Service of Bosowa Corporation - Dian Gita Utami; Syachriani Syam; Asri Essada Nurachmah (Business Journal : Jurnal Bisnis Dan Sosial, 2023)
Bosowa Corporation and other substantial businesses have a diverse portfolio of companies and brands, people today are becoming more and more conscious of the importance of brands as marketing tools. In order to maximise total brand equity for its brands and goods, Bosowa must have a brand architecture and branding strategy. This study will go into detail on brand architecture and branding strategy for Bosowa Corporation's goods and services, particularly those that are B2C (business to customer) and sold solely in Makassar. Information on company strategy, brand equity, market dynamics, and audit portfolio is used as input to gain a general picture of the operations and performance of Bosowa brands. Any brand portfolio-related issues that Bosowa Corporation faces will be formulated with the use of a SWOT analysis.